2018
DOI: 10.7189/jogh.08.010602
|View full text |Cite
|
Sign up to set email alerts
|

Validity of maternal report of care-seeking for childhood illness

Abstract: BackgroundAccurate data on care-seeking for child illness are needed to improve public health programs and reduce child mortality. The accuracy of maternal report of care-seeking for child illness as collected through household surveys has not been validated.MethodsA 2016 survey compared reported care-seeking against a gold-standard of health care provider documented care-seeking events among a random sample of mothers of children <5 years in Southern Province, Zambia. Enrolled children were assigned cards wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…Similarly, there is limited published research on the impact on effective coverage measures of including non-facility or non-public providers – important sources of care in some settings – in the provider survey sampling frame [8]. Two previous studies in this Collection have compared exact-match and ecological linking methods for delivery care and sick child care to assess the validity of ecological linking methods for coverage estimation [13,14]. Willey et al found that in one district of Uganda, ecological linking methods that accounted for provider type resulted in better agreement with exact match linking methods, relative to ecological linking only by administrative area [14].…”
mentioning
confidence: 99%
“…Similarly, there is limited published research on the impact on effective coverage measures of including non-facility or non-public providers – important sources of care in some settings – in the provider survey sampling frame [8]. Two previous studies in this Collection have compared exact-match and ecological linking methods for delivery care and sick child care to assess the validity of ecological linking methods for coverage estimation [13,14]. Willey et al found that in one district of Uganda, ecological linking methods that accounted for provider type resulted in better agreement with exact match linking methods, relative to ecological linking only by administrative area [14].…”
mentioning
confidence: 99%
“…First, data on childhood illness and related care-seeking behavior during the previous two weeks were collected during participant interviews and may be subject to a combination of recall and social desirability bias. A recent study of the validity of maternally-reported care-seeking for childhood illness found that the indicator had both high sensitivity and specificity, resulting in only a minor overestimation of care-seeking relative to true levels [46]. Previous experience within this study area noted the potential for underreporting of sensitive health behaviors (eg, abortion services), especially when solicited through a survey-based approach [47], though this bias is likely reduced when asking about less sensitive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The intention of this paper is to describe a methodology that we hope will contribute to higher quality and greater standardization of validation studies of intervention coverage measures – their design, analysis, and interpretation. The recommendations result from our experience over the last 7 years conducting 10 validation studies in diverse settings [ 13 , 16 - 19 , 21 , 28 , 29 ] thus not every study follows all recommendations presented here. For example, earlier studies 1) used the term “reference standard” vs our now recommended “gold standard”, accepting that any gold standard will have limitations; 2) used a cut-off of AUC≥0.6, which we decided was too low and increased to AUC≥0.7; 3) did not always publish the percent of don’t know responses; 4) did not present the results for the percent agreement between respondent reports and the gold standard for indicators for which validation results could not be presented due to sample size; and 5) used a variety of different graphics to illustrate results vs the graphs provided in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is often conducted by a trained clinician, such as a nurse or nurse/midwife [ 13 , 14 ]. Provider medical records may also be considered the gold standard for some validation studies, if of sufficiently high quality [ 15 ], or may be used to complement other gold standard methods [ 16 ]. Validation studies for careseeking indicators may employ GPS tracking, barcoded ID cards, physical tokens, or other methods for documenting patient visits to health providers in the study area [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation